American journal of education (Chicago, IL : University of Chicago Press, 2020)
1.Design Thinking, Leadership, and the Grammar of Schooling: Implications for Educational Change. LEA HUBBARD, AMANDA DATNOW A growing number of schools across the globe have implemented design think. ing (DT) as an instructional approach to increase student engagement, motivate creative thinking, and teach students to problem solve. Although offering significant opportunity to students, implementing DT can involve pushing against the traditional "grammar of schooling." Drawing on in-depth qualitative case study data, we present findings on a previously low-performing, under enrolled middle school that underwent a dramatic shift when becoming a magnet school focused on DT. We explain the intentional leadership actions that facilitated structural and cultural changes, including building a collaborative leadership structure. Interactions between the principal and the teachers led to the emergence of practices that supported innovation schoolwide. At the same time, internal and external challenges rooted in the grammar of schooling arose, requiring educators to respond to sustain the momentum for change. Implications for policy and practice are discussed.--2.A Neoliberal Grammar of Schooling? How a Progressive Charter School Moved toward Market Values ELISE CASTILLO Although initially ideologically diverse, the charter school movement has become increasingly aligned with neoliberal ideology, which assumes that public services, including education, are improved through market forces, such as accountability, competition, efficiency, and managerialism. Yet lite is known about how leaders of ideologically progressive charter schools sustain their founding pedagogical and political missions amid widespread market values. This qualitative case study of one progressive charter school in New York City investigates this phenomenon. Findings demonstrate that the school's enrollment, instructional, school governance, and community engagement practices moved toward market values as school leaders and board trustees prioritized attaining favorable test outcomes, garnering resources, and ensuring the renewal of the school's charter. Findings illustrate a neoliberal grammar of schooling, or powerful forces that led school leaders to move their practices toward market values, in turn constraining the realization of the school's founding progressive mission.--3.Rethinking the Grammar of Student-Teacher Relationships.HILLARY L. GREENE NOLAN One educational structure with its own grammar is the student-teacher relationship. The conventional relational grammar involves teachers and students connecting to pursue academic learning-a grammar rooted in both historic attempts to define the professional domain of teaching as the transmission of academic knowledge as well as current efforts to "learnify" education. This study describes 154 student-teacher relationships experienced by three high school teachers in a Midwest middle college to depict a revised relational grammar. Encouraged to reimagine teaching as academic and nonacademic support-giving, the Lincoln teachers exhibited a relational grammar based on knowing students as learners and also deeply as people and giving nonacademic support as much as or more than academic support, with implications for equity.--4.Institutional Logics in Los Angeles Schools: Do Multiple Models Disrupt the Grammar of Schooling? JULIE A. MARSH, TAYLOR N. ALLBRIGHT, KATRINA E. BULKLEY, KATE E. KENNEDY and TASMINDA K. DHALIWAL The structure of US public education is changing. Rather than exclusive district management of schools with standardized programs, new types of systems have emerged. In the case of "portfolio" systems, advocates argue that choice, performance-based accountability, and autonomy challenge traditional schooling and foster a diversity of options for parents. Yet there is limited empirical evidence on these claims. Our mixed-methods study examines the values and reported practices of schools in Los Angeles, We find limited evidence of variation across schools. Rather, institutional forces appear to be shaping common commitments to academics, whole child support, community, and professionalism, with some fine-grained differences connected to organizational characteristics. Ultimately, this lack of diversity and the complexity of multiple logics do not appear to challenge the idea of a shared "grammar of schooling" across schools. This research advances our understanding of institutional logics in schools and provides implications for policy and future research.